PENGARUH BERBAGAI KONSENTRASI EKSTRAK BIJI ADAS (Foeniculum vulgare mill.) SEBAGAI DENTURE CLEANSER TERHADAP PERTUMBUHAN CANDIDA ALBICANS PADA PLAT AKRILIK - Andhika Ambo; Arlina Nurhapsari; Erwid Fatchur Rahman (ODONTO : Dental Journal, 2015)
Introduction: Fennel plant is known as a medicine plant. Fennel plant parts that have the highest content is the seed. Essential oils, flavonoids, and saponins contained in fennel seed have an influence against candida albicans growth.Purpose: This study was conducted to determine the influence of various concentrations of fennel seed extract as a denture  cleanser against candida albicans growth on acrilyc plate.Methods: This research was an experimental laboratoty and study design was an experimental with post test only control group design. Total sample is 30 acrilyc plate measuring 6x1 cm. The sample were divided into 6 groups, 5 groups were  soaked in various concentrations of fennel seed extract (20%, 40%, 60%, 80%, 100%) and one groups was soaked in control positive polident. Soaking was done for 5 minutes. Candida  albicans were incubated for 48 hours at 37°C. The result of this study were analyzed by one-way ANOVA and LSD (Least  Significance Difference).Results: Based on the one-way ANOVA test was done then  obtained significance value of 0,000 (p<0,05), so it can be concluded that there are significant differences between the two sets groups of at least. Based on the LSD test was done then obtained significance value of p<0,05 in all groups which means there are significant differences between each group, except in group fennel seed extract concentration of 100% with control  positive polident obtained 0,924 significance (p>0,05) which means there are no significant differences between two groups.Conclusion: The researchers' conclusion that there was the influence of various concentration of fennel seed extract as a denture cleanser against candida albicans growth on aclilyc plate. Fennel seed extract concentration of 100% has the  greatest influence as a denture cleanser against candida albicans growth.